Graft-derived cell free DNA: used for assessment of early graft status and its implications for long-term kidney function - Wei, Liang; Zhao, Yongheng; Deng, Shaoping; Wu, Shaoping; Wang, Hailian; Luo, Xiangwei; Yang, Hongji (Frontiers in Physiology, 2024)
BackgroundThe long-term graft survival is closely related to its early status, yet the indices for assessing the early graft status are complex and lack quantitative values. The aim of this study is to investigate the potential of GcfDNA as a comprehensive, non-invasive, convenient, and quantifiable indicator for evaluating early graft status.MethodsIn this study, 138 recipients who underwent primary kidney transplantation were enrolled. Peripheral blood samples, each 10 mL, were collected on days 1 and 7 post-transplantation. The quantification of both the graft cell-free DNA (GcfDNA) fraction (%) and GcfDNA concentration (copies per milliliter, cp/mL) was performed using droplet digital PCR (ddPCR).ResultsFor most recipients, both the GcfDNA fraction and concentration had a rapid decline at 7 days post-transplantation, reaching median values of approximately 0.7% and 53.5 cp/mL, respectively. No significant associations were found between GcfDNA values and other clinical parameters. On the seventh postoperative day, we observed a significant elevation in GcfDNA concentration among recipients with eGFR values < 60 mL/min/1.73 m2. Additionally, notable increases were identified in both GcfDNA fraction and concentration variations within this specific subgroup. The findings of our study indicate a negative correlation between the concentration and fractional changes of GcfDNA on postoperative days 1 and 7, as well as the GcfDNA concentration on postoperative day 7, with eGFR within the 1–2 years post-transplantation period. The ROC curve of GcfDNA_Copies_Variation. day1-day 7 showed the highest AUC value AUC = 0.8006, with high sensitivity (90.14%) and specificity (77.61%), and PPV and NPV were 81.01% and 88.14%, respectively. Using four classical algorithm models, we found that the xgboost regression model achieved the best predictive performance (area under the curve (AUC) values = 0.862) for eGFR within 1–2 years post-transplantation, with high sensitivity (85.7%) and specificity (85%).ConclusionThe changes of GcfDNA levels in the early stage are closely related to kidney function within 1–2 years post-transplantation. As a comprehensive indicator of graft function, GcfDNA has great potential for clinical application.